Searching for an English self through writing - Karlsson, Leena (Studies in Second Language Learning and Teaching, 2015)
Most Finnish university students, just like the other new global elites (Kramsch, 2013), use English without problems. Some students, however, struggle with English to the extent that their studies suffer. One could say that they have a deeply “wounded” English self (Karlsson, 2013). My context of research and practice is the Autonomous Learning Modules (ALMS) at Helsinki University Language Centre. In my work as a language counsellor and practitioner-researcher, pedagogical concerns are always primary, and there is a need to appreciate diversity yet notice every student’s unique experiences. The broad background of my recent work is English as part of the identity of young academic Finns. In particular, I have been interested in how students with a “wounded” English self can develop new identity positions, and in how a language counsellor can help them in this process. In this paper, my focus is on the subtle practical interconnections between learner autonomy, learner diversity, and learner identity as they emerge in a diary written by a student of English with dyslexia and language (classroom) anxiety. A narrative case study of Mariia illustrates how the counsellor’s appreciation and her own recognition of the complex ecological realities (Casanave, 2012) surrounding and interacting with her learning encourage and empower her. Mariia uses her freedom to control her own learning (Huang & Benson, 2013) and makes choices from the many lifewide experiential learning opportunities in her life (Karlsson & Kjisik, 2011). Reflective writing in the learning diary helps her to construct a realistic vision of herself as a learner and user of English, and she leaves the identity position of a failure in the classroom and claims a new, more successful one (Norton, 2014).